Detection of Enterococcus Faecalis in subgingival biofilm of patients with chronic refractory periodontitis - Balaei-Gajan, E.; Shirmohammadi, A.; Abashov, R.; Agazadeh, M.; Faramarzie, M. (Medicina oral, patología oral y cirugía bucal, 2010)
Refractory periodontitis is the occurrence of additional clinical attachment loss after repeated attempts to control the infection with conventional periodontal therapy. Some microorganisms seem to be involved in the pathogenesis of chronic refractory periodontitis. The prevalence of Enterococcus faecalis in the oral cavity seems to be higher in individuals with periodontitis. Therefore, the present study investigated the presence of E. faecalis in subgingival biofilm of patients with chronic refractory periodontal disease. Periodontal treatment was instituted for 100 patients suffering from chronic periodontitis. Then samples were obtained from 27 successfully treated and 27 chronic refractory periodontitis subjects and then cultured. Statistical evaluation was performed for descriptive purposes. 27% of the patients had chronic refractory periodontitis. The difference in the presence of E. faecalis in the pockets between the successfully treated (11.1%) and chronic refractory (51.8%) groups by culture methods was statistically significant (p<0.05). Data showed that E. faecalis is probably involved in the pathogenesis of refractory periodontitis. Accurate knowledge about the pathogen and its role in the pathogenesis of refractory infections helps develop effective treating strategies.